POPULASI DAN INTENSITAS SERANGAN HAMA WERENG HIJAU Nephotettix virescens (HOMOPTERA; CICADELIDAE) DI KECAMATAN TOMOHON BARAT KOTA TOMOHON - Tuldenigsri H. Gigir; Christina Salakie; Emmy Senewe (Universitas Sam Ratulangi, 2015)
ABSTRACT In North Sulawesi, there are several major insect pests of rice plants, one of which is green leafhoppers which often cause damage to the rice crop. Aside from being a green planthopper pests also act as an insect vector that can transmit the disease Tungro. The study aims to determine the intensity of pest populations of green leafhoppers N. virescens on rice crops in West Tomohon sub district. The research was conducted in two villages namely Tara-tara and Woloan in the District of West Tomohon Tomohon. The research was conducted from December 2014 through April 2015. This study used a survey method in two villages, namely Tara-tara and Woloan West Tomohon sub district Tomohon. The results showed that the population of green leafhopper pest Nephoettix virescens on rice crops in the district of West Tomohon, Tomohon, is highest in sub Tara tara on observations II, as many as 8.5 tails and lowest in sub Woloan on observations IV, namely 2.3 tail. In general, the population of planthoppers in paddy rice crops in the district of West Tomohon, Tomohon highest average of Tara-tara Village, which is 5.8 tails Woloan Village only 4.9 tails. The intensity of the green leafhopper pest N. virescens on rice crops in the district of West Tomohon, Tomohon, is highest in sub Tara-tara on observations IV, amounting to 29.83 % and the lowest in the sub Woloan the first observation, namely 9.83 %. In general, the intensity of plant hopper pest on rice crops in the district of West Tomohon Tomohon highest average in Tara-tara Village, which is 24.89 % and Woloan Village only 14.89 %. Keyword : Freen Planthopper Nephotettix virescens, Paddy, Tomohon